Emerging tick-borne infections in mainland China: an increasing public health threat. Issue 12 (December 2015) - Fang, Li-Qun; Liu, Kun; Li, Xin-Lou; Liang, Song; Yang, Yang; Yao, Hong-Wu; Sun, Ruo-Xi; Sun, Ye; Chen, Wan-Jun; Zuo, Shu-Qing; Ma, Mai-Juan; Li, Hao; et al.
Summary: Since the beginning of the 1980s, 33 emerging tick-borne agents have been identified in mainland China, including eight species of spotted fever group rickettsiae, seven species in the family Anaplasmataceae, six genospecies in the complex Borrelia burgdorferi sensu lato, 11 species of Babesia, and the virus causing severe fever with thrombocytopenia syndrome. In this Review we have mapped the geographical distributions of human cases of infection. 15 of the 33 emerging tick-borne agents have been reported to cause human disease, and their clinical characteristics have been described. The non-specific clinical manifestations caused by tick-borne pathogens present a major diagnostic challenge and most physicians are unfamiliar with the many tick-borne diseases that present with non-specific symptoms in the early stages of the illness. Advances in and application of modern molecular techniques should help with identification of emerging tick-borne pathogens and improve laboratory diagnosis of human infections. We expect that more novel tick-borne infections in ticks and animals will be identified and additional emerging tick-borne diseases in human beings will be discovered.